Declined circular RNA mitofusin 2 constrains the deterioration of Wilms tumor via modulating microRNA-372-3p/transforming growth factor-β receptor type 2 axis: CircRNA MFN2 and WT - Xiao, Maolin; Pu, Xiaofeng; Tong, Wei; Xiao, Xiao (Cellular and Molecular Biology, 2024)
To explore the action and mechanism in which circular RNA (circRNA) mitofusin 2 (MFN2) repressed the malignant proliferation of Wilms tumor (WT) via modulating microRNA (miR)-372-3p/transforming growth factor-β receptor type 2 (TGFBR2) axis. CircRNA MFN2 was distinctly elevated in the tissues and cells of WT patients, while miR-372-3p was silenced in the tissues and cells of WT. Test of TGFBR2, PCNA and Bax was implemented. Transfection with si-circRNA MFN2 or miR-372-3p-mimic restrained cancer cell advancement and the number of PCNA content was declined, while transfection with miR-372-3p-inhibitor was opposite, and PCNA content was augmented. MiR-372-3p-inhibitor turned around si-circRNA MFN2’s therapeutic action after co-transfection with si-circRNA MFN2 + miR-372-3p-inhibitor. Ultimately, it was verified that circRNA MFN2 was negatively associated with miR-372-3p, which was negatively linked with TGFBR2, and circRNA MFN2 was positively associated with TGFBR2. To sum up, the results of this research illuminated circRNA MFN2 repressed WT’s malignant proliferation via modulating miR-372-3p/TGFBR2 axis.